SPEECH ERROR IN “GET REAL GIVING THANKS WITH SAM KIM EP #22 BY DIVE STUDIOS” VIDEO PODCAST - Ruth Intan Angraeni Tampubolon; Syahron Lubis (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
The study aims to describe the speech errors and find out the causes of the speech errors in the video podcast Get Real Giving thanks with Sam Kim Ep 22. The researchers collected data using the documentation method and applied qualitative analysis. The data for this research were the utterances from the video podcast Get Real Giving thanks with Sam Kim Ep 22. The data source was a video between the hosts, Ashley and BM, and the guest, Sam Kim, which was downloaded from the official DIVE Studios YouTube Channel with durations of 46 minutes. The data were described based on the theory of Common Speech Errors by Clark Clark (1977). According to the results, it was shown that Ashley made nine types of errors totaling 47 errors, but BM made eight types, so he did not make errors in types of stutters totaling 80 errors, and Sam made nine types totaling 106 errors. The causes of the speech errors are due to internal and external factors such as nervousness, hesitation, haste, and lacking concentration. The total number of speech errors made by the speakers is 233 mistakes. The speech errors happened as many as 52 repetitions, and Sam did it the most. In filled pause, 46 mistakes occurred, and Sam as well as BM produced the most errors. In silent pause, 41 errors occurred 41, and all speakers made the errors. In interjections, 37 mistakes occurred, and Ashley made the fewest mistakes. In false starts (unretraced), 14 mistakes occurred, and BM as well as Ashley made 4 mistakes. In corrections, 13 mistakes occurred, and BM only made two mistakes. In stutters, 13 mistakes happened, and Asley and Sam made the most mistakes, but BM did not make any mistake. In a slip of the tongue, 11 mistakes occurred, and Ashley made only one mistake. In false starts (retraced), which is the least common type, 6 mistakes occurred.